Vertebrate TNF Superfamily: Evolution and Functional Insights - Ignacio Marín (Biology)
This study characterizes the evolution of the tumor necrosis factor superfamily (TNFSF) across vertebrate lineages, both cyclostomes and gnathostomes, by combining sequence similarity and synteny data for the genes from 23 model species. The available evidence supports a simple model in which most of the diversity found in living species can be attributed to the expansion of four genes found in an ancestor of all vertebrates before the first of the genome duplications that occurred in the vertebrate lineages. It is inferred that the ancestor of all cyclostomes possessed only six TNFSF genes. A cyclostome-specific genome triplication had little effect on the total number of these genes. The ancestor of all gnathostomes, due to the effect of a second genome duplication plus additional single-gene duplications, already had 21 TNFSF genes. In several gnathostome lineages, particularly in some tetrapods, the TNF superfamily has significantly contracted due to numerous gene losses. This evolutionary model provides a framework for exploring functional data, showing that the descendants of different ancestral genes have acquired distinct roles, most prominently in the innate and adaptive immune systems, which led to a species-specific refinement of which TNFSF genes were conserved or lost. Several data hitherto difficult to interpret (the interactions of very different TNFSF ligands with the same receptors; the ability of the same ligands to bind alternative receptors, with or without death domains; and the cooperation of different ligands in specific functions) can be explained as consequences of the evolutionary history of the TNF superfamily.